Quantitative Phytochemical Analysis of Ethanol Extract Kelulut Bee Propolis (Trigona laeviceps) - Yusrinie Wasiaturrahmah; Maharani Laylliza Apriasari; Cita Nursyaina Tasya (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Kelulut bees are widely bred in Kalimantan. These bees do not have a stinger and easily adapt to new environments. Another characteristic of the kelulut bee is that it produces more propolis than honey. Kelulut Bee propolis contains tannins, alkaloids, flavonoids, and phenolics bioactive compounds with the potential to heal drugs. Following the concept of 'Back to Nature', namely increasing public interest in using natural ingredients to be used as medicine. Therefore, a test is needed to strengthen the utilization of this potential and quantitative phytochemical analysis is needed to determine the levels of each compound in kelulut bee propolis. The purpose of this research was to analyze the results of the quantitative phytochemical of ethanol extract of kelulut bee propolis (Trigona laeviceps). The research used non- experimental research with quantitative laboratory examination to analyze sample content. The results showed he quantitative phytochemical analysis of ethanol extract of kelulut bee propolis (Trigona laeviceps) showed a content of tannin compound 1.85 mg/ml, alkaloid 154.31 mg/ml, flavonoid 56.83 mg/ml and phenolic 120.37 mg/ml. Ethanol extract of bee propolis (Trigona laeviceps) showed a tannin compound content of 1.85 mg/ml, alkaloids 154.31 mg/ml, flavonoids 56.83 mg/ml and phenolic 120.37 mg/ml. Alkaloid had the highest concentration of 154.31 mg/ml, while tannin had the lowest concentration of 1.85 mg/ml.